Sky Alert! When Satellites Fail - Johnson, Les.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
How much do we depend on space satellites? Defense, travel, agriculture, weather forecasting, mobile phones and broadband, commerce...the list seems endless. But what would our live be like if the unimaginable happened and, by accident or design, those space assets disappeared? Sky Alert! explores what our world would be like, looking in turn at areas where the loss could have catastrophic effects. The book - demonstrates our dependence on space technology and satellites; - outlines the effect on our economy, defense, and daily lives if satellites and orbiting spacecraft were destroyed; - illustrates the danger of dead satellites, spent rocket stages, and space debris colliding with a functioning satellites; - demonstrates the threat of dramatically increased radiation levels associated with geomagnetic storms; - introduces space as a potential area of conflict between nations.
From the Contents: Part I: How we might lose our Satellites -- Orbital Debris -- War.-Part II: If we were to lose our satellites -- The Global Positioning System (Military Uses) -- Economic Fallout from the Losing the Global Positioning System -- GPS and the Average Person -- Spy Satellites and Military Reconnaissance -- Communications -- Weather Forecasting -- Remote Sensing - Resource Monitoring and Locating -- Remote Sensing - Environmental Monitoring and Science -- Part III: What Can We Do? -- Reduce the Growth of Orbital Debris.
Keywords: Engineering; Remote sensing; Astronomy; Astronautics; Telecommunication; Economics; Engineering; Aerospace Technology and Astronautics; Popular Science in Astronomy; Security Science and Technology; Communications Engineering, Networks; Remote Sensing/Photogrammetry.; Economics general